Sustainable business models in the grocery trade in Finland: a multiple case study : Sustainability in grocery trade - a discourse analysis - Lauronen, Milja-Rebekka (My University, 2022)
This paper studies sustainable business models in the Finnish grocery trade. Grocery trade has experienced changes in recent years due to the pandemic, and the impacts of sustainability are a rising trend in the 2000s. The study’s theoretical backgroud builds on defining sustainability as a phenomenon from the historical perspective. Other themes in the theoretical part of the study are sustainable strategy, and, in detail, sustainable business models. The study focuses on implementing the Triple-layered Business model canvas (TLBMC) framework according to the business models of case companies. The case companies of the study are the three companies with the largest market shares in the Finnish grocery trade: K Group, S Group and Lidl. The total market share of the companies consists of over 90 percent of the sales in the grocery trade. The research method for the study is a qualitative multiple case study. The study’s data is based on secondary data sources: annual reports, press releases and other documents. The empirical part of the study is formulated as within-case analyses of each case company, following a cross-case analysis of findings in all case companies. The theoretical framework for the empirical part is the TLBMC tool, where the findings according to the data are placed and analyzed. The final part of the thesis comprises the discussion and conclusions of the paper. The discussion is based on the study’s empirical results, where the conclusions are formed according to the analyses conducted in the empirical context. Lastly, the managerial implications and limitations of the study are presented. In addition, the suggestions for future research are covered in the last chapter of the thesis.
Keywords: business models; enterprises; sustainable development; business; models (objects); corporate strategies; Finland; food supply chains; case study; business operations; grocery stores; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development